Online Addictions: Conceptualizations, Debates, and Controversies - Griffiths, Mark D.; Pontes, Halley M.; Kuss, Daria J. (Addicta: The Turkish Journal on Addictions, 2016)
The activity of play has endured throughout human history and more recently, the Internet has emerged as a playground increasingly populated by gamblers, gamers, shoppers, and social networkers. Research suggests that a minority of online users experience symptoms traditionally associated with substance-related addictions, including mood modification, tolerance, conflict, and salience. Previous research suggests that a combination of individual, situational, and structural characteristics determine whether, and to what extent, individuals engage in various online activities. For instance, it is believed that access, affordability, and anonymity are critical factors that make the Internet viable for the acquisition, development, and maintenance of online addictions. Since the current scientific knowledge of online addiction is copious in scope and appears relatively complex, this paper examines a selection of the main debates in the field, the conceptualization of excessive online behavior as an addiction, and other key controversies. Citation: Griffiths, M. D., Pontes, H. M., & Kuss, D. J. (2016). Online addictions: Conceptualizations, debates, and controversies. Addicta: The Turkish Journal on Addictions, 3, 151‒164. http://dx.doi.org/10.15805/addicta.2016.3.0101